Islamic education teacher’s perception of the curriculum integration during online teaching and learning - Ismail, Halim; Abu Hassan, Muhammad Ikram (KOED IIUM, 2022)
The closure of higher education institutions and schools due to the COVID-19 Pandemic has affected the structure of teaching and learning (PDP), that is, from the method of teaching and learning (PDP) directly to teaching and learning at home (PDPR) via online. This study was conducted to identify teachers' perceptions of the curriculum integration during online teaching and learning sessions of the Islamic Education Secondary School Standard Curriculum (KSSM) subject. The methodology used in this study is qualitative in nature and involves interviews and document analysis. This study found that curriculum integration needs to be implemented during the teaching and learning process, but there are some shortcomings that need to be improved in terms of implementation to be in line with the requirements of the curriculum and philosophy of Islamic Education. This study has an impact on the teaching methods of Islamic education teachers in Malaysia during PDPR in terms of curriculum integration.